2019
DOI: 10.3389/fonc.2019.00794
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cancer Through the Lens of Epigenetic Inheritance, Allele-Specific Gene Expression, and High-Throughput Technology

Abstract: Epigenetic information is characterized by its stable transmission during mitotic cell divisions and plasticity during development and differentiation. This duality is in contrast to genetic information, which is stable and identical in all cells in an organism with exception of immunoglobulin gene rearrangements in lymphocytes and somatic mutations in cancer cells. Allele-specific analysis of gene expression and epigenetic modifications provides a unique approach to studying epigenetic regulation in normal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…The use-it or lose-it model accounts forwithout depending onthe role of epigenetic changes in favoring the onset of evolved adaptations (78). Epigenetic mechanisms, such as DNA methylation or small RNA-mediated epigenetic modifications, can help directly regulate the proposed coordinated antagonistic expression of P A and P B (105, 106) (Figure 1) and may be inherited (107). It can also account for the adaptive contribution of spatial and temporal non-genetic heterogeneity in populations of genetically narrow or uniform cells (28,108,109).…”
Section: The Use-it or Lose-it Model Of Adaptive Evolution Has Considerable Explanatory Power And Makes Testable Predictionsmentioning
confidence: 99%
“…The use-it or lose-it model accounts forwithout depending onthe role of epigenetic changes in favoring the onset of evolved adaptations (78). Epigenetic mechanisms, such as DNA methylation or small RNA-mediated epigenetic modifications, can help directly regulate the proposed coordinated antagonistic expression of P A and P B (105, 106) (Figure 1) and may be inherited (107). It can also account for the adaptive contribution of spatial and temporal non-genetic heterogeneity in populations of genetically narrow or uniform cells (28,108,109).…”
Section: The Use-it or Lose-it Model Of Adaptive Evolution Has Considerable Explanatory Power And Makes Testable Predictionsmentioning
confidence: 99%
“…Epigenetics has become a primary research field over the past several years [7]. According to prior research [8], DNA and histone modification are the focuses in epigenetics. A growing number of studies have revealed various modifications of mRNAs during 5-capping and 3-tailing 4-6 under exon splicing [9], such as N6-methyladenosine (m6A) and N1-methyladenosine (m1A), as well as pseudouridine methylation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Histone modifications together with DNA methylation and demethylation constitute the blossoming field of epigenetics, which harbors great promise as these agents are able to modify gene expression genome-wide, thus acting similarly ubiquitously as transcription factors such as p53 or MYC. Not surprisingly, these types of genes are also frequently mutated in the cancer genome, constituting one major finding of the whole-genome mutation analysis studies within TCGA projects or by other efforts [91,92].…”
Section: Pathway Pathology and Treatmentmentioning
confidence: 99%